Euro Area Policies : Financial Sector Assessment Program-Technical Note-Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2018)
The SSM (SSM) has made a solid start. Set up a little over three years ago, the SSM has developed into a coherent banking supervision mechanism operating across the 19 Euro Area Member States. Banking supervision at the European Central Bank (ECB) is underpinned by a clear mandate and independence from government or industry interference in individual supervisory decisions. Its well-defined supervisory methodology and processes-complemented by committed staff-have laid the foundations for more forward-looking, pre-emptive, and evenhanded supervision. This is a noteworthy achievement for the Euro Area.